GUIDE TO THE ESSENTIALS IN EMERGENCY MEDICINE - Ooi, Shirley; Low, Matthew; Manning, Peter (McGraw-Hill Education (Asia), 2022)
This book aims to achieve a fine balance between a practical evidence-based tool, that can be carried around to be used at the patients' bedside, and a comprehensive reference with sufficient information for examination requirements in Emergency Medicine, both at undergraduate and postgraduate level. This edition preserves several of its predecessor's hallmark features, in particular: Easy-to-read format: clinical descriptions are presented succinctly, key points are highlighted, and problems are introduced with a symptom-based approach in Part 1; Popular sections such as Caveats, covering pitfalls likely to be encountered in clinical practice, and Special Tips for GPs. New features of this edition include: Clear demarcation between chapters for basic learners (medical students) and advanced learners, with 805 pages for basic learners and advanced chapters marked with blue bars on the sides; Thorough revision of all chapters, including more comprehensive illustrations; 9 additional brand-new chapters, including 3 chapters on emergency CT interpretation; QR codes to: more than 100 between clinical photos, radiological images and videos; reference chapters, to ensure that the extra information is available without making the book too voluminous.